Multiomics Analysis Reveals the Prognostic Non-tumor Cell Landscape in Glioblastoma Niches - Xiao, Zixuan; Zhang, Wei; Li, Guanzhang; Li, Wendong; Li, Lin; Sun, Ting; He, Yufei; Liu, Guang; Wang, Lu; Han, Xiaohan; Wen, Hao; Liu, Yong; et al. (Frontiers in Genetics, 2021)
A comprehensive characterization of non-tumor cells in the niches of primary glioblastoma is not fully established yet. This study aims to present an overview of non-malignant cells in the complex microenvironment of glioblastoma with detailed characterizations of their prognostic effects. We curate 540 gene signatures covering a total of 64 non-tumor cell types. Cell type-specific expression patterns are interrogated by normalized enrichment score (NES) across four large gene expression profiling cohorts of glioblastoma with a total number of 967 cases. The GBMs in each cohort are hierarchically clustered into negative or positive immune response classes with significantly different overall survival. Our results show that astrocytes, macrophages, monocytes, NKTs, and MSC are risk factors, while CD8 T cells, CD8 naive T cells, and plasma cells are protective factors. Moreover, we find that the immune system and organogenesis are uniformly enriched in negative immune response clusters, in contrast to the enrichment of nervous system in positive immune response clusters. Mesenchymal differentiation is also observed in the negative immune response clusters. High enrichment status of macrophages in negative immune response clusters are independently validated by analyzing scRNA-seq data from eight high-grade gliomas, revealing that negative immune response samples comprised 46.63% to 55.12% of macrophages, whereas positive immune response samples comprised only 1.70% to 8.12%, with IHC staining of samples from six short-term and six long-term survivors of GBMs confirming the results.